Pemikiran Teologi Ekonomi Islam di Indonesia Pada Era 4.0 - Ahyani, Hisam; Slamet, Memet; Mutmainah, Naeli (INAIFAS Press, 2022)
ABSTRACT Thoughts in Islamic economic theology in the 4.0 era as now in Indonesia adhere to economic freedom, meaning that this freedom is required to always be Muslim-friendly. This research method uses the Library Research method and collects data obtained by means of a literature study from books and journals relevant to the study of the theological conception of Islamic Economics in Indonesia Era 4.0. The findings prove that Islamic Economic Theological Thought Concept of Islamic Economic Theological Thought is a concept formed in order to realize the aspirations of Muslims regarding economic issues in which the concept of Islamic economic theology has a significant effect on its adherents in concrete life. Such as bermu'amalah in terms of Islamic legal politics, Islamic Economic Politics, development strategies in halal tourism, halal food, cash waqf transactions and so on. Regarding independence from lust as a form of effort to escape from the shackles of human (negative) lust, it means that humans as human beings are required to always use their minds. Islamic Economics as a Choice for a Muslim for several reasons, namely the principles adopted by the theological concepts that are adopted by the Islamic economic community itself, especially in Indonesia.